2002
DOI: 10.1007/s00244-001-0056-8
|View full text |Cite
|
Sign up to set email alerts
|

Accumulations of Nitrite and Nitrate in the Tissues of Penaeus monodon Exposed to a Combined Environment of Elevated Nitrite and Nitrate

Abstract: Penaeus monodon (11.86 +/- 0.63 g) exposed individually to six different nitrite and nitrate regimes [nitrite at 0.002 (control), 0.360, and 1.455 mM combined with nitrate at 0.005 (control) and 7.275 mM] in 25 ppt sea water were examined for the nitrite and nitrate concentrations in tissues and nitrite uptake and nitrate uptake after 24 h in 25.3 degrees C. In P. monodon following exposure to 1.455 mM nitrite only, nitrite levels increased by factors of 0.33, 1.05, 1.36, 1.79, 2.10, 2.16, 2.21, and 3.58 in mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Also, Sarıkaya et al (2006) found that the effect of nitrite was higher than nitrate. Cheng and Chen (2002) conducted a study with the Asian tiger shrimp Panaeus monodon and applied NaNO2 and NaNO3 to these organisms. They investigated the accumulation of nitrite and nitrate in the tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, Sarıkaya et al (2006) found that the effect of nitrite was higher than nitrate. Cheng and Chen (2002) conducted a study with the Asian tiger shrimp Panaeus monodon and applied NaNO2 and NaNO3 to these organisms. They investigated the accumulation of nitrite and nitrate in the tissues.…”
Section: Discussionmentioning
confidence: 99%
“…They investigated the accumulation of nitrite and nitrate in the tissues. Cheng and Chen (2002) found out that nitrite and nitrate have similar toxicological mechanisms but nitrite accumulates in the tissues more than nitrate. In addition, it is stated that organisms convert nitrate to nitrite and toxicity occurs in this way.…”
Section: Discussionmentioning
confidence: 99%
“…Because of organic food particles and no aeration of test solutions over the exposure period, dissolved oxygen dropped to as low as 2 mg/L in some treatments, including controls, despite solution renewals at 24-h intervals. Ammonia levels were high because of metabolic waste coincident with feeding activity, and previous studies have shown that ambient nitrate concentrations can significantly increase ammonia excretion in penaeid shrimp [28].…”
Section: Binary Mixture Bioassays With Foodmentioning
confidence: 98%
“…In crabs, nitrate can cross the gills, sometimes against a concentration gradient, by substituting for chloride (Cl) in the chloride-bicarbonate exchange mechanism that normally regulates the osmotic and respiratory functions of the gill (Lee and Pritchard 1985; Onken et al 2003). The ability of the gill epithelium of freshwater fish to accumulate Cl − suggests that nitrate can also accumulate, as shown in tiger prawns (Cheng and Chen 2002). Thus, as is the case with chloride, the circulating nitrate concentration can exceed that of the surrounding water.…”
mentioning
confidence: 98%